Papan Partisi Dari Limbah Kertas - Vincentius Khrisna (Intra, 2017)
Paper waste is a commodity that is used by many people, especially in the academic environment of University, many students are using paper to support of their study activities, this causes a large amount of paper is thrown away after they finish their academic activities, therefore a lot of paper are not reused and become paper waste which is useless. In response to this problem, the researcher tries to utilize the paper waste in University to be reused using “Recycle” Method to turn paper waste into partition board to replace multiplex. This research used experimental research method to find a suitabl composition of specimens in order that the partition borad of the paper waste can be strong and stable to replace the use of multiplex in furniture.